2002
DOI: 10.1159/000065509
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Spectral Analysis of Sleep EEG in Acute Hemispheric Stroke

Abstract: Background: Reports on the effects of focal hemispheric damage on sleep EEG are rare and contradictory. Patients and Methods: Twenty patients (mean age ± SD 53 ± 14 years) with a first acute hemispheric stroke and no sleep apnea were studied. Stroke severity [National Institute of Health Stroke Scale (NIHSS)], volume (diffusion-weighted brain MRI), and short-term outcome (Rankin score) were assessed. Within the first 8 days after stroke onset, 1–3 sleep EEG recordings per patient were performed. Sleep scoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
50
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 28 publications
3
50
0
6
Order By: Relevance
“…Muller et al found a lower sleep efficiency, as well as lower amounts of SWS and REM sleep in patients with acute hemispheric stroke 17 . Gottselig et al 18 documented a reduced spindle activity on the side of the lesion in patients with extra-thalamic stroke.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Muller et al found a lower sleep efficiency, as well as lower amounts of SWS and REM sleep in patients with acute hemispheric stroke 17 . Gottselig et al 18 documented a reduced spindle activity on the side of the lesion in patients with extra-thalamic stroke.…”
Section: Introductionmentioning
confidence: 96%
“…Changes in sleep EEG patterns after hemispheric stroke have been documented in studies of the last three decades [12][13][14][15][16][17][18][19] . Muller et al found a lower sleep efficiency, as well as lower amounts of SWS and REM sleep in patients with acute hemispheric stroke 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies report a reduction in sleep efficiency and increased wakefulness after sleep onset [3,4,5,6,7], with [3] or without [8] a reduction in total sleep time. Stage II is found to be reduced [3, 6] or even increased [8, 9], and similar results are reported for slow wave sleep (SWS) [3, 6,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there is no evidence for the relation of stroke severity to sleep architecture. Regarding the outcome, certain sleep features have been associated with poor prognosis, namely reduced sleep efficiency and total sleep time, increased 24-hour sleep and reduced sleep spindles, K complexes and sleep stages II, REM and SWS [3, 5, 8, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…This usually results in an infarct in the brain, which comprises dead tissues due to the stroke. The detailed information about the location and volume of the infarcts is crucial to a number of stroke-related research questions, such as predicting prognosis, Manuscript identifying chronic functional deficits [3]- [7], or investigating sleep problems of stroke patients [8], [9]. In addition, the availability of a lesion mask may also be beneficial to analyses of functional MRI [10] and diffusion tensor imaging.…”
mentioning
confidence: 99%